Getting a better look: Outcomes of laparoscopic versus transdiaphragmatic pericardial window for penetrating thoracoabdominal trauma at a Level I trauma center. Issue 6 (December 2016) - Anderson, Jamie E.; Salcedo, Edgardo S.; Rounds, Kacie M.; Galante, Joseph M.
Abstract : BACKGROUND: In penetrating thoracoabdominal trauma, it is necessary to evaluate both the pericardial fluid and the diaphragm directly. Transdiaphragmatic pericardial windows (TDWs) provide direct access to the pericardium and diaphragm but expose the patient to the risks of laparotomy. We hypothesize that transabdominal laparoscopic pericardial windows (LPWs) are a safe and effective alternative to TDWs in stable patients. METHODS: This is a retrospective observational study of stable patients with thoracoabdominal penetrating trauma at a level I trauma center between January 2007 and June 2015, comparing outcomes after TDW versus LPW. RESULTS: A total of 99 patients with penetrating trauma had a diagnostic pericardial window, 33 of which were laparoscopic. Stab wounds were most common (80, 80.8%) compared with gunshot wounds (19, 19.2%). Of 11 patients who had a positive pericardial window, 10 (90.9%) were associated with a cardiac injury. There was no difference in the ratio of positive pericardial windows for patients who had TDW versus LPW (8/66, 12.1% vs. 3/33, 9.1%; p = 0.651). One patient had a complication related to a negative pericardial window in the laparoscopic group. There was no difference in complication rates between TDW and LPW ( p = 0.155). Mean length of stay was longer in TDW compared with LPW (12 vs. 5 days, p = 0.046). One patient died during index admission in the TDW group, but there was no difference in mortality rates between TDW and LPW during the index admission ( p = 0.477). Median length of follow-up was 29 days (range, 0–2, 709). On long-term follow-up, there was also no difference in mortality rates between TDW and LPW (2/66, 3.0% vs. 2/33, 6.1%; p = 0.470). CONCLUSION: In hemodynamically stable patients with thoracoabdominal injuries, LPW is a safe and effective technique in evaluating both pericardial fluid and the diaphragm. LPW is a viable alternative to exploratory laparotomy and TDWs. LEVEL OF EVIDENCE: Therapeutic study, level IV.